On being a client understanding the process of counselling and psychotherapy - Howe, David 1946-
'On Being a Client' identifies a number of clear and potent messages that transcend the complexity of counselling thought and psychotherapeutic practice. Using clients' experiences as a framework, the author creates a general theory of counselling and psychotherapy. He proposes that the social and psychological structures which generate the clients' experiences underlie all psychotherapeutic encounters, and the self forms and reforms in social relationships - including those established in the therapeutic context